2015
DOI: 10.1111/opo.12254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the Shin‐Nippon SRW‐5000 autorefractor in adults: an update

Abstract: The SRW-5000 and its derivatives have been, and continue to be, of significant importance in our drive to understand myopia progression, myopia control techniques, and oculomotor function in human vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…In order to minimise the effects of proximal accommodation and to promote a relaxed accommodative state, a binocular open field autorefractor with a fixation target positioned at 6 m was employed. The measurement of refractive error using the Shin‐Nippon open field autorefractor has been reported to be within 0.50 DS of the subjective refraction measured in a cohort of a similar age …”
Section: Discussionmentioning
confidence: 76%
“…In order to minimise the effects of proximal accommodation and to promote a relaxed accommodative state, a binocular open field autorefractor with a fixation target positioned at 6 m was employed. The measurement of refractive error using the Shin‐Nippon open field autorefractor has been reported to be within 0.50 DS of the subjective refraction measured in a cohort of a similar age …”
Section: Discussionmentioning
confidence: 76%
“…It has since undergone a number of developments to improve its clinical and research utility and has been used widely in optometry and vision science. 26 Several clinical evaluations of the Grand Seiko (WAM-5500, WR-5100K) found that its measurements were very similar to those from a subjective refraction (mean difference within 0.15 D) over a wide range of refractive error (−15 to 6.5 D) in adults. 12, 14, 27, 28 Choong and colleagues 10 found that the Grand Seiko WR-5100K provided similar measurement of SE as a subjective refraction (−0.44 D vs −0.37 D, P = 0.21) in 7- to 12-year-olds (N = 117).…”
Section: Discussionmentioning
confidence: 96%
“…Journal of Ophthalmology VX110 measurement is not influencing the accommodation stimulus because it is thought that a closed-field environment could overestimate myopia [19]. Also, it is necessary to check if these autorefractors could replace conventional subjective refraction since the objective refraction of the Eye Refract presented similar efficacy to subjective refraction [26].…”
Section: Discussionmentioning
confidence: 99%
“…Binocular open-field traditional autorefractors were developed to avoid myopia that a monocular closed-field environment may be generated without cycloplegia [19].…”
Section: Introductionmentioning
confidence: 99%